Фізико-хемічний стан поверхні стопу ВТ6 після піскоструминного оброблення у рідкому азоті - Васильєв, М.О.; Яценко, Л.Ф.; Волошко, С.М.; Гурин, П.О. (Металлофизика и новейшие технологии, 2016)
Вперше піскоструминне оброблення (ПО) поверхні титанового стопу ВТ6 проведено за температури рідкого азоту (-196°C). Для порівняння використано також стандартну схему ПО на повітрі за аналогічних параметрів та тривалости. Показано, що основні відмінності стосуються змін мікротвердости, шерсткости, характеру морфології, кількости залишкових частинок абразиву Al₂O₃ на поверхні. Докладно досліджено хемічний склад у різних локальних ділянках поверхні стопу після ПО за кімнатної та кріогенної температур, а також ступінь їх окиснення. Впервые пескоструйная обработка (ПО) поверхности титанового сплава ВТ6 проведена при температуре жидкого азота (-196°C). Для сравнения использована также стандартная схема ПО на воздухе при аналогичных параметрах и продолжительности. Показано, что основные различия касаются изменений микротвёрдости, шероховатости, характера морфологии, количества остаточных частиц абразива Al₂O₃ на поверхности. Подробно исследованы химический состав в различных локальных участках поверхности сплава после ПО при комнатной и криогенной температурах, а также степень их окисления. Firstly, the sand blasting (SB) of the titanium alloy Ti6Al4V surface at the temperature of liquid nitrogen (-196°C) is performed. For comparison, a standard treatment is used as the SB in the air under the same parameters and duration. As shown, the major differences concern microhardness changes, roughness, character of morphology, and amount of the residual abrasive particles of Al₂O₃ on the surface. The chemical composition in the different local areas of the alloy surface after the SB at room and cryogenic temperatures is studied in detail as well as a degree of surface oxidation. It is planned to obtain experimental evidence regarding the fact that the low-temperature SB improves the wear resistance of dental implants in chewing loads, the corrosion resistance, and the adhesion strength of biocompatible coatings applied to titanium substrate after the SB in liquid nitrogen, and thus, contributes significantly longer service life.